A novel process for molasses utilization by membrane filtration and resin adsorption. (10th January 2019) - Qiang, Xiufu; Luo, Jianquan; Guo, Shiwei; Cao, Weifeng; Hang, Xiaofeng; Liu, Junsheng; Wan, Yinhua
Abstract: Cane molasses is mainly used for ethanolic fermentation but a large amount of wastewater with refractory pigments and highly concentrated salts limited its application. For the first time, we attempt to directly extract pigments from molasses, and an integrated process consisting of ceramic membrane clarification, nonpolar resin adsorption and loose nanofiltration purification was proposed for recovery and fractionation of the molasses pigments. A 300 KDa ultrafiltration membrane was preferred for clarification of the pretreated molasses due to high permeate flux and low irreversible fouling, which could improve the quality of the extracted pigments. The nonpolar macroporous resin was chosen for only extracting the hydrophobic caramel pigments in order to reduce the resin regeneration frequency and improve the pigment purity, where ethanol was used for resin regeneration as it was easy to separate and reuse. The resin adsorption could reduce hydrophobic fouling formation and reappear the "salt-induced pore swelling" effect on the nanofiltration membrane, thus decreasing operating pressure by 50% at 60 °C and increasing the sucrose/salt transmission during diafiltration (save diafiltration water by 27%). The polyphenol pigments were obtained in the nanofiltration retentate after removing sugar and salts by diafiltration, and the permeate could be further desalted to produce syrup drinking. This novel integrated process could not only recover two natural pigments in a clean way, but also save energy and water consumption during the nanofiltration separation, which provided a sustainable strategy to utilize cane molasses. Graphical abstract: Image 1 Highlights: A suitable pore size of ceramic membrane is vital to permeate flux and fouling control. Nonpolar resin adsorption extracts the hydrophobic caramel pigments. Resin adsorption decreases NF operating pressure and increases sucrose/salt transmission. Loose NF can well separate pigments and sugar/salt by diafiltration at 60 °C. The integrated process provides a green and sustainable way to utilize cane molasses.